Diagnostic and surgical dilemma of cholecystitis that mimics cancer – A case report of xanthogranulomatous cholecystitis. (2020) - Lee, Alex; Forse, Catherine L.; Walsh, Cynthia; Bertens, Kimberly; Balaa, Fady
Highlights: Xanthogranulomatous cholecystitis (XGC) is a benign disease that can mimic cancer. Management is complicated by uncharacteristic presentation and imaging findings. Surgeons must ensure counselling includes the possibility of both XGC and carcinoma. Abstract: Introduction: Xanthogranulomatous cholecystitis (XGC) is a rare and benign chronic inflammatory disease of the gallbladder that can mimic carcinoma on presentation, imaging, and gross pathology. The aim of this case report is to describe the considerations involved in navigating the diagnostic and surgical dilemma of managing XGC in a patient with findings equivocal to gallbladder cancer. Presentation of case: A 64-year-old female patient presented with an incidental, suspicious gallbladder mass on imaging. Due to her asymptomatic presentation and high risk features for carcinoma on imaging, an oncologic, en-bloc resection of the mass involving the gallbladder, liver, wall of duodenum, and hepatic flexure of the colon was performed. On pathological examination, the gallbladder specimen showed marked lymphohistiocytic inflammatory infiltrate of XGC that extended into adjacent structures without dysplasia. The patient had an uncomplicated postoperative course. Discussion: Considerations around management of XGC must include the potential consequences associated with overtreating a benign entity or undertreating a potentially curable malignancy. Imaging findings that may be more suggestive of XGC include continuous mucosal lines and the presence of pericholecystic infiltration or fat stranding. Pitfalls of biopsy include potential tumour spillage and false negative results, especially when both XGC and cancer are present. Intraoperatively, macroscopic examination of the mass can also be misleading. Conclusion: Surgeons must ensure that preoperative counselling includes the possibility of both XGC and gallbladder carcinoma, especially when findings are uncharacteristic. XGC must be managed with careful consideration of all findings and multidisciplinary input from a team of surgeons, radiologists, and pathologists.